Determinants of quality of life of cancer patients at a tertiary care medical city in Riyadh, Saudi Arabia - AlJaffar, Mohammed A.; Enani, Sari S.; Almadani, Ahmad H.; Albuqami, Fay H.; Alsaleh, Khalid A.; Alosaimi, Fahad D. (Frontiers in Psychiatry, 2023)
Background Incidences of cancer are increasing at an unprecedented rate in Saudi Arabia, making it a major public health concern. Cancer patients are faced with physical, psychological, social, and economic challenges, all of which can impact quality of life (QoL). Objectives This study aims to explore the sociodemographic, psychological, clinical, cultural, and personal factors that could affect the overall QoL of cancer patients. Methods A total of 276 cancer patients who attended the King Saud University Medical City's oncology outpatient clinics between January 2018 to December 2019 were included. QoL was assessed with the Arabic version of the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire-C30. Psychosocial factors were assessed with several validated scales. Results QoL was poorer among patients who were female (p = 0.001), have visited a psychiatrist (p = 0.028); were taking psychiatric medications (p = 0.022); and had experienced anxiety (p < 0.001), depression (p < 0.001), and distress (p < 0.001). The most used method to self-treat was Islamic Ruqya (spiritual healing; 48.6%), and the most often perceived cause for developing cancer was evil eye or magic (28.6%). Good QoL outcomes were associated with biological treatment (p = 0.034) and satisfaction with health care (p = 0.001). A regression analysis showed that female sex, depression, and dissatisfaction with health care were independently associated with poor QoL. Conclusions This study demonstrates that several factors could influence cancer patients' QoL. For instance, female sex, depression, and dissatisfaction with health care were all predictors of poor QoL. Our findings support the need for more programs and interventions to improve the social services for cancer patients, along with the need to explore the social difficulties oncology patients face and address such obstacles through improving social services by expanding the scope of social workers' contribution. Larger multicenter longitudinal studies are warranted to examine the generalizability of the results.